Higher Education and the Gendering of Space in England and Wales, 1869-1909 - Oman, Georgia (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book offers a spatial history of the decades in which women entered the universities as students for the first time. Through focusing on several different types of spaces - such as learning spaces, leisure spaces, and commuting spaces - it argues that the nuances and realities of everyday life for both men and women students during this period can be found in the physical environments in which this education took place, as declaring women eligible for admittance and degrees did not automatically usher in coeducation on equal terms. It posits that the intersection of gender and space played an integral role in shaping the physical and social landscape of higher education in England and Wales in the late-nineteenth and early-twentieth centuries, whether explicitly - as epitomised by the building of single-sex colleges - or implicitly, through assumed behavioural norms and practices. Georgia Oman holds a PhD in History from the University of Cambridge, UK. Her research has been published in the Women's History Review.
Introduction -- 1. 'The prestige attending a stately and ornamental pile': The campus ideal -- 2. 'To have a study of my own': The question of residence -- 3. 'They do not walk much about the city alone': Class, commuting, and the city -- 4. 'Gazed at as if we were a new species': Libraries, laboratories and learning spaces -- 5. 'Let no man enter on pain of death': Sport, soirées, and social spaces -- 6. 'Under one roof, but otherwise completely separate': Unions, guilds and extra-curricular spaces -- Conclusion.
Keywords: Women -- History; Great Britain -- History; Education -- History; Women's History / History of Gender; History of Britain and Ireland; History of Education